1961
DOI: 10.1111/j.1476-5381.1961.tb01100.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF THE FUNCTIONAL EFFECTS OF DYFLOS, TRI‐O‐CRESYL PHOSPHATE AND TRI‐p‐ETHYLPHENYL PHOSPHATE IN CHICKENS

Abstract: Tri-p-ethylphenyl phosphate is unique amongst the organophosphorus compounds which produce neurotoxic effects in not being an inhibitor of cholinesterase. The dysfunction it produces is also marked by some unusual features. Thus it produces a characteristic high-stepping gait which develops at varying periods after intramuscular injection but more regularly following oral administration. A careful comparison of the character, onset and development of the effects of diisopropyl phosphorofluoridate (dyflos), tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1962
1962
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The oral LDJ-Q was determined and was found to be 540 mg/kg. A single dose of 8,12,16,40,80,160,240 For the second part of the experiment 3 groups of Nucles chicken (30 hens each) were used. Two groups were subjected to repeated daily oral doses of either 1.5 or 3 mg/bird/day, respectively, while the third group was used as a control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral LDJ-Q was determined and was found to be 540 mg/kg. A single dose of 8,12,16,40,80,160,240 For the second part of the experiment 3 groups of Nucles chicken (30 hens each) were used. Two groups were subjected to repeated daily oral doses of either 1.5 or 3 mg/bird/day, respectively, while the third group was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Human exposure to some of these chemicals could lead to injury of the nervous system involving axonal and/or myelin disruption. The clinical symptoms termed "delayed neurotoxicity" are usually not seen until [8][9][10][11][12][13][14] days after exposure 1 . Newly discovered compounds are subjected to condensed studies in an attempt to detect those with maximum effect to insects and other pests without any side effect to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of neurotoxicity associated with organic phos phorus compounds have attempted to learn which molecu lar configurations are capable of producing the phenomenon and which are not. When active compounds were investi gated qualitatively, it was found that a sufficiently low dos age was tolerated, and progressively larger dosages increased the frequency and severity, and often reduced the latency of neurotoxicity (Aldridge and Barnes, 1961;Cavanagh et al, 1961;Davies et al, 1960;Siegel et al, 1965). Hayes (1991) points out the timedependence of neuro toxicity, but also that clearcut quantitative relationships have not been found, perhaps because they have not been sought.…”
Section: 2 Neurotoxicitymentioning
confidence: 97%
“…A similar dose-dependent pattern appeared with metabolite-treated birds except that marked weight loss did not result until after the appearance of marked muscle weakness. Cavanagh (unpublished observations, cited by Cavanagh, Davies, Holland & Lancaster, 1961) has noted that decreasing the tri-o-cresyl phosphate dose reduced the extent of damage to the peripheral nerves to a greater degree than it did to the long tracts of the spinal cord. The dose differential in affecting the peripheral nerves in contrast to the spinal cord appeared to be even greater for the metabolite.…”
Section: Discussionmentioning
confidence: 99%